2022
DOI: 10.3389/fimmu.2022.885829
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Accelerates the Recovery of Hepatitis B Virus-Related Acute-on-Chronic Liver Failure by Promoting M2-Like Transition of Monocytes

Abstract: Background and AimAcute-on-chronic liver failure (ACLF) has a high mortality rate. The role of granulocyte colony-stimulating factor (G-CSF) in ACLF remains controversial. Monocytes/macrophages are core immune cells, which are involved in the initiation and progression of liver failure; however, the effect of G-CSF on monocytes/macrophages is unclear. The study aimed to verify the clinical efficacy of G-CSF and explore the effect of it on monocytes in hepatitis B virus (HBV)-related ACLF (HBV-ACLF) paitents.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…G-CSF is a hematopoietic growth factor and stimulates neutrophil development and differentiation 37 . G-CSF therapy has been used in HBV associated acute on chronic liver failure, and some Asian studies have found improved liver function and survival rates in patients receiving this treatment 38 , 39 . However, a European multicentre study on acute on chronic liver failure of different etiologies failed to demonstrate any positive effect of G-CSF therapy 40 .…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is a hematopoietic growth factor and stimulates neutrophil development and differentiation 37 . G-CSF therapy has been used in HBV associated acute on chronic liver failure, and some Asian studies have found improved liver function and survival rates in patients receiving this treatment 38 , 39 . However, a European multicentre study on acute on chronic liver failure of different etiologies failed to demonstrate any positive effect of G-CSF therapy 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-colony stimulating factor are primarily produced by monocytes, fibroblasts and endothelial cells of the stroma of the bone marrow ( 62 ). G-CSF can encourage monocytes to convert to an anti-inflammatory/pro-restorative phenotype (M2-like) ( 63 ), and could aid in prompt clearance of HBV ( 64 ) be inferred that G-CSF may aid in viral clearance during chronic infections. Myeloid lineage cells need GM-CSF in order to proliferate, differentiate, and survive ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 90-day cumulative liver transplantation free survival rate in Tα1 was 75% compared to 53.4% in the standard medical therapy group (P = 0.03), and the incidence of complications such as bacterial infection and hepatic encephalopathy was lower in the Tα1 group (32.1%) compared to the standard treatment group (58.6%) (P = 0.029) 17 . Granulocyte Colony Stimulating Factor (G-CSF) was compared to standard therapy in in a randomized control trial of 114 HBV-ACLF patients, and the G-CSF group was shown at 180 days to have greater survival (72.2 vs. 53.8%, P 0.014) 18 . However, aside from immediately starting antiviral therapy for ACLF-HBV, these newer modalities are still under investigation and cannot be recommended.…”
Section: Acute Liver Failure Patientsmentioning
confidence: 99%